KOLEKSI RHODODENDRON SEBAGAI SALAH SATU TAMAN TEMATIK DI KEBUN RAYA ‘EKA KARYA’ BALI - Putri, D.M.S. (Buletin Udayana Mengabdi, 2018)
Rhododendron has been widely used as an ornamental plant and an important horticultural commodity; be it original or hybridized. In Bali Botanic Gardens, the use and utilization of Rhododendron as one of thematic theme park aesthetically and functional with attention to two fundamental things that function of park based on spatial concept and activity that can support task and function of Bali Botanic Gardens; and the use of art and design elements